Stress analysis of steam turbine rotor using Fluid-Structure Interaction simulation - Fauzi, Katanda Fajar; Choiron, Moch. Agus; Widodo, Agung Sugeng; Irawan, Yudy Surya; Darmadi, Djarot B.; Purnowidodo, Anindito (GMPI Conference Series, 2024)
Steam Power Plant generates electricity due to a device that extracts heat energy from steam and converts it into mechanical work on the rotor. Turbines operate at high pressures and temperatures which may cause potential failures in the rotor. This study aims to determine the stress distribution on the turbine rotor to predict potential failures. The turbine studied is a 15 MW steam turbine with a rotation speed of 3000 rpm, inlet steam pressure of 2 MPa, and inlet steam temperature of 471.2 OC. The study focused on the Curtis stage. Fluid-Structure Interaction (FSI) simulation was performed to determine the interaction between the fluid and the turbine rotor. Computational Fluid Dynamic (CFD) was performed to determine the temperature and pressure hitting the rotor. The temperature and pressure distribution data from the CFD simulation is transferred to the structural simulation as the load received by the rotor. In addition to fluid loads, the rotor experiences centrifugal loads due to rotation and gravity loads. The largest stress received by the turbine rotor is at the front of the rotor with a stress of 347.39 MPa.